Prevalence of recent occupational injury and its associated factors among food industry workers in Selangor - Dapari, Rahmat (Public Library of Science, 2023)
Malaysia’s gross domestic product is heavily influenced by the food and beverage sector and the contribution of the industry to the national economy is expected to increase in the coming years. Thus, the need for employees in the food industry will continue to rise as this sector grows. Nevertheless, employees in the food industry are exposed to various occupational hazards that can lead to occupational injuries, mainly related to kitchen work. Given the increasing number of employees in the food industry and the rising trend of occupational injuries, this study was conducted to determine the prevalence of recent occupational injuries and their associated factors and predictors among food industry workers.